Dickkopf-3 Contributes to the Regulation of Anti-Tumor Immune Responses by Mesenchymal Stem Cells - Lu, Kun-Hui; Tounsi, Amel; Shridhar, Naveen; Küblbeck, Günter; Klevenz, Alexandra; Prokosch, Sandra; Bald, Tobias; Tüting, Thomas; Arnold, Bernd (Frontiers in Immunology, 2015)
Mesenchymal stem cells (MSCs) are known to limit immune responses in vivo by multiple soluble factors. Dickkopf-3 (DKK3), a secreted glycoprotein, has recently been identified as a novel immune modulator. Since DKK3 has been reported to be produced by MSCs we investigated whether DKK3 contributes to the immune suppression of anti-tumor responses by MSCs. Whereas wild-type MSCs inhibited immune responses against two different transplantation tumors, DKK3-deficient MSCs did not affect the rejection process. Increased CD8+ T cell and reduced M2-type macrophages infiltration was observed in tumors inoculated together with DKK3-deficient MSCs. Thus, DKK3 could alter the composition of the tumor stroma, thereby supporting the MSCs-mediated suppression of immune responses against these tumor transplants.